Mangas as a strategic resource in english language teaching - COSTA, Gleuciane Milena Delduch da (2023)
The presents work is about the importance of the manga as strategic resource in English language teaching. This work is based on a qualitative and exploratory research approach. The research was carried out based on documents analyzed on the Google Docs and Scielo digital platforms, in Portuguese and English. The objective in this work is the use of manga in the classroom as a resource strategy, will be analyzes aspects such as the historicity, the characteristics, its relevance in society, the reason to study manga in school is to show the importance of Manga for education, and the use of manga as a didactic alternative in English language classes, stimulating reading and allowing interdisciplinary themes to be worked on, and we will see the importance of manga for motivation, memorization and how it would be interesting to approach transversal themes through its narratives.